Trade flows and trade specialisation: The case of China - Guglielmo Maria Caporale; Anamaria Sova; Robert Sova (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
Using annual data for the period 1992-2012, this paper examines trade flows between China and its main trade partners in Asia, North America and Europe, and whether increasing trade has led to industrial structural adjustment and changes in China's trade patterns. The analysis is based on both economic indicators and the estimation of a gravity model, and applies recently developed panel data methods that explicitly take into account unobserved heterogeneity, specifically the fixed effect vector decomposition (FEVD) technique. The findings confirm the significant change in China's trading structure associated with the fast growth of foreign trade. In particular, there has been a shift from resource- and labour-intensive to capital- and technology-intensive exports.
Keywords: C23; F14; F15; 330; gravity model; panel data analysis; trade specialisation; comparative advantage